2014
DOI: 10.1007/978-3-319-11839-0_1
|View full text |Cite
|
Sign up to set email alerts
|

How Do You Like Your Virtual Agent?: Human-Agent Interaction Experience through Nonverbal Features and Personality Traits

Abstract: Abstract. Recent studies suggest that human interaction experience with virtual agents can be, to a very large degree, described by people's personality traits. Moreover, the nonverbal behavior of a person has been known to indicate several social constructs in different settings. In this study, we analyze human-agent interaction from the perspective of the personality of the human and the nonverbal behaviors he/she displays during the interaction. Based on existing work in psychology, we designed and recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…For this experiment’s non-responsive ECA, we didn’t expect effects of rapport, but the outcome measure was added for exploratory and verification purposes. The Rapport scale (Cerekovic et al, 2014) consists of fifteen items and we used a seven-point Likert scale ranging from [(1) – Disagree strongly to (7) – Agree strongly].…”
Section: Methodsmentioning
confidence: 99%
“…For this experiment’s non-responsive ECA, we didn’t expect effects of rapport, but the outcome measure was added for exploratory and verification purposes. The Rapport scale (Cerekovic et al, 2014) consists of fifteen items and we used a seven-point Likert scale ranging from [(1) – Disagree strongly to (7) – Agree strongly].…”
Section: Methodsmentioning
confidence: 99%
“…It could be useful in applications for career development and counseling in the human resources or academic areas [30,31], adaptive e-learning systems [32], diagnosis of mental health disorders (borderline personality disorder [33], depression [3], schizophrenia [34], eating disorder [35] or sleep disorders [36]), virtual psychologist applications [37], and personalized health assistance [38]. It was also shown that there are links between common physical diseases (such as heart attacks, diabetes, cancer, strokes, arthritis, hypertension, and respiratory disease) and Big Five personality traits [39] such that these diseases influence the age-related personality accelerating with 2.5 years decrease for extraversion, 5 years decrease for conscientiousness, 1.6 years decrease for openness, and 1.9 years increase for emotional stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, an agent can simulate several traits, Cerekovic et al [5] evaluated the effects of two different virtual agents, one with a high level of neuroticism and other with a high level of extroversion, and the role of the agent's nonverbal cues combined with personality traits to improve Human-Agent Interaction (HAI). They also measured the participants' personality using the Big Five questionnaire [16] to analyse how trait combination influenced participants' preference towards one character versus the other.…”
Section: Persuasion Using Personalitymentioning
confidence: 99%